AFM/FFM study of micro/nano-tribological properties of Diamond-Like Carbon film. (28th April 2008) - Fan, Zhen; Ding, Jianning; Ling, Zhiyong; Xie, Guoxin
Micro-tribological properties of different Diamond Like Carbon (DLC) thin films were studied with the AFM/FFM. The surface topographies of the prepared specimens were observed by AFM, and the adhesive forces were also measured. The results indicate that the friction coefficient of the tested DLC film depends on the combined effect of the adhesion and the sample roughness. The friction force increases over velocity when the scanning velocity is not high, due to the effect of stick-slip behaviour, but their relationship is reversed with the increase of the velocity which is caused by the phase transformation of the DLC films.